Plasmonic reflection color filters with metallic random nanostructures. (23rd January 2017) - Wu, Q J; Jia, H; Hu, X L; Sun, L B; Wang, L S; Yang, S M; Tai, R Z; Fecht, H J; Wang, L Q; Zhang, D X; Jiang, J Z
Abstract: We develop reflective color filters with randomly distributed nanodisks and nanoholes fabricated with hydrogen silsesquioxane and Ag films on silicon substrate. They exhibit high resolution, angle-independence and easily up-scalable fabrication, which are the most important factors for color filters for industrial applications. We uncover the underlying mechanism after systematically analyzing the localized surface plasmon polariton coupling in the electric-field distribution. The agreement of the experimental results with those from the simulation indicates that tunable colors across the visible spectrum can be obtained by simply varying the diameter of the nanodisks, promoting their applications.